Directive UtterancesIn Islamic Holy Scripture Chapter Al -A'raf(A Pragmatics Perspective) - SIAHAAN, INTAN DWI GABETTA (2016)
ABSTRACT INTAN DWI GABETTA SIAHAAN. A320120060. DIRECTIVE UTTERANCES IN ISLAMIC HOLY SCRIPTURE CHAPTER AL -A'RAF (A PRAGMATICS PERSPECTIVE). Research Paper, School of Teacher Training and Education Faculty. Muhammadiyah University of Surakarta. January, 2016. The research aims at describing the intention, implicature, and flouting maxim of directive utterance in Islamic Holy Scripture. The research employs descriptive qualitative as the type of research. Data source of this research is the script of Islamic Holy Scripture. Techniques of collecting data are reading English version data in Islamic Holy Scripture chapter Al-A'raf, searching sentences containing utterances, selecting data containing directive utterances, and coding the data script. Techniques of data analysis are describing the intention contained in the directive utterance in Islamic Holy Scripture chapter Al-A'raf by refering to the theory of speech act from Kreidler(1989), describing the implicature contained in the directive utterance in Islamic Holy Scripture chapter Al-A'raf by refering to the theory of implicature from Levinson(2000), and describing the maxims violated contained in the directive utterance in Islamic Holy Scripture chapter Al-A'raf by refering to the theory of maxim from Grice (1975). The data are shown with the italic and underline words. One datum analysis presents intention, implicature and flouting maxim analysis. The result of the study shows that 1) The categories of intention are: commanding(50%), requesting(26%), suggestion(10%), prohibition(2%), ordering(12%). 2) The implicature of directive utterances cover conventional(50%) and conversational (50%). Conversational implicature divided into: particularized(77%) and generalized(23%). 3) The flouting maxim are used: quality(8%), relative(54%), and manner (38%). Keywords : directive utterance, implicature, Islamic Holy Scripture, and maxim violated.